Analisis Potensi Virtual reality sebagai Strategi Pemasaran Pariwisata Kota Pagar Alam - Arif Prambayun; Della Oktaviany; Yunita Fauzia Achmad (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The purpose of this study is to describe virtual reality as a tourism marketing strategy, analyze in-depth to understand the concept of virtual reality, its role, and potential that can be used as a tourism marketing strategy to increase tourist visits to Pagar Alam City. This paper systematically integrates relevant research in existing fields, builds a research framework, and conducts a situa-tional analysis of virtual reality technology as a tourism promotion strategy through SWOT analy-sis. Based on the SWOT analysis, we tried to connect the potential of virtual reality with market-ing theory, to find the advantages of using virtual reality as a tourism marketing strategy to in-crease the attractiveness of tourist visits in the city of Pagar Alam in particular. The city of Pagar Alam as a tourist destination with 24 natural attractions and 27 cultural attractions, has good strengths and opportunities to take advantage of VR-based tourism strategies, these various tour-ist objects can be visualized well and in detail through a virtual environment so that they can in-fluence the desire of tourists to visit Pagar Alam city. Although the opportunities offered by VR in the tourism sector, especially in the city of Pagar Alam, are quite significant, there are still many challenges and problems that must be solved. One of them is about infrastructure readiness and awareness of tourism industry players in utilizing VR technology. This research was only con-ducted based on literature review publications collected in recent years and analyzed tourism in the city of Pagar Alam from the aspect of using digital information technology, promotional strategies, and government policies.